PRODUCTION AND CHARACTERIZATION OF THREE BRUCELLA ANTIGENS, LIPOPOL- YSACCHRIDE (LPS), SONICATED CELLS AND WHOLE CELLS ANTIGEN - RAOUF MAHDI , NITHAL (The Iraqi Journal of Veterinary Medicine, 1996)
Three types of Brucella abortus antigens were prepared: Lipopolysaccharide (LPS), sonicated cells and whole cells killed antigens. Enzyme-linked immunosorbent assay (ELSIA) was carried out in polysterene microtiter plates using horse-radish peroxidase conjugated to anti- normal bovine serum globuline with hydrogen peroxide and ortho-phenylenediamine as hydrogen as substrate. The results showed that the whole Brucella cells antigen gave the best distinguish between the positive and negative sera with lowest cross reactive with E. coli antiserum